Seroprevalence of Hepatitis E Virus in Domestic Pigs and Wild Boars in Switzerland. (6th February 2014) - Burri, C.; Vial, F.; Ryser‐Degiorgis, M.‐P.; Schwermer, H.; Darling, K.; Reist, M.; Wu, N.; Beerli, O.; Schöning, J.; Cavassini, M.; Waldvogel, A.
Summary Hepatitis E is considered an emerging human viral disease in industrialized countries. Studies from Switzerland report a human seroprevalence of hepatitis E virus (HEV) of 2.6–21%, a range lower than in adjacent European countries. The aim of this study was to determine whether HEV seroprevalence in domestic pigs and wild boars is also lower in Switzerland and whether it is increasing and thus indicating that this zoonotic viral infection is emerging. Serum samples collected from 2, 001 pigs in 2006 and 2011 and from 303 wild boars from 2008 to 2012 were analysed by ELISA for the presence of HEV‐specific antibodies. Overall HEV seroprevalence was 58.1% in domestic pigs and 12.5% in wild boars. Prevalence in domestic pigs was significantly higher in 2006 than in 2011. In conclusion, HEV seroprevalence in domestic pigs and wild boars in Switzerland is comparable with the seroprevalence in other countries and not increasing. Therefore, prevalence of HEV in humans must be related to other factors than prevalence in pigs or wild boars.